Electrocatalytic Difunctionalization of Olefins as a General Approach to the Synthesis of Vicinal Diamines - Parry, Joseph B.; Fu, Niankai; Lin, Song (Synlett, 2018)
Vicinal diamines are highly prevalent structural motifs in therapeutic agents, bioactive natural products, and molecular catalysts. However, there are currently few unified methodological approaches for making these pertinent synthetic building blocks. This Synpacts article provides an overview of selected landmark developments in the area of olefin diamination. In particular, we highlight our recent contribution on the electrocatalytic diazidation of olefins as a general, selective, and sustainable method for the synthesis of vicinal diamines.1 Introduction2 Background: Intermolecular Diamination of Olefins3 Background: Intermolecular Diazidation of Olefins4 Electrocatalytic Diazidation of Olefins
Keywords: diamines; diazidation; electrochemistry; electrocatalysis; radicals